2006
DOI: 10.1242/dev.02301
|View full text |Cite
|
Sign up to set email alerts
|

EARLY IN SHORT DAYS 1(ESD1) encodes ACTIN-RELATED PROTEIN 6 (AtARP6), a putative component of chromatin remodelling complexes that positively regulatesFLCaccumulation inArabidopsis

Abstract: We have characterized Arabidopsis esd1 mutations, which cause early flowering independently of photoperiod, moderate increase of hypocotyl length, shortened inflorescence internodes, and altered leaf and flower development. Phenotypic analyses of double mutants with mutations at different loci of the flowering inductive pathways suggest that esd1 abolishes the FLC-mediated late flowering phenotype of plants carrying active alleles of FRI and of mutants of the autonomous pathway. We found that ESD1 is required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
172
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(192 citation statements)
references
References 91 publications
15
172
0
5
Order By: Relevance
“…By contrast, the mutations cause the suppression of the developmentally regulated FLC gene, supporting the positive role of H2A. Z (Martin-Trillo et al, 2006;Choi et al, 2007;Deal et al, 2007;March-Díaz et al, 2007).…”
Section: Recruitment Of Chromatin Modification Factors and General Trmentioning
confidence: 72%
“…By contrast, the mutations cause the suppression of the developmentally regulated FLC gene, supporting the positive role of H2A. Z (Martin-Trillo et al, 2006;Choi et al, 2007;Deal et al, 2007;March-Díaz et al, 2007).…”
Section: Recruitment Of Chromatin Modification Factors and General Trmentioning
confidence: 72%
“…This complex is involved in the substitution of histone H2A by the histone variant H2A.Z (March-Díaz and Reyes, 2009). Indeed, mutations in PIE1, ARP6 (also known as SUF3 and ESD1 in Arabidopsis), and SEF/ AtSW6C show early flowering and reduced FLC expression (Noh and Amasino, 2003;Choi et al, 2005Choi et al, , 2007Deal et al, 2005;Martin-Trillo et al, 2006;March-Díaz et al, 2007;Lázaro et al, 2008), and ARP6 and PIE1 were found to be required for H2A.Z deposition at FLC (Deal et al, 2007). Finally, it has been shown that disruption of BRM results in high FLC expression and that the brm mutation restores high accumulation of FLC mRNA in pie and sef mutants, suggesting that SWR1/SCRAP and SWI/SNF complexes play antagonistic roles in FLC regulation (Farrona et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in Arabidopsis showed that loss-of-function mutations in two genes encoding putative homologs of components of the SWR1/SRCAP complex, ACTIN-RELATED PROTEIN6 (ARP6) and the Snf2 protein PHOTOPERIOD-INDEPENDENT EARLY FLOWERING1 (PIE1), led to premature flowering as a result of reduced FLC expression (Noh and Amasino, 2003;Choi et al, 2005;Deal et al, 2005;Martin-Trillo et al, 2006). However, the mechanism by which these proteins regulate FLC expression has not been addressed.…”
Section: Introductionmentioning
confidence: 99%